METODE PERTANGGUNG JAWABAN PENGGUNAAN DANA HIBAH PEMILU: Studi Kasus KPU Deli Serdang - Dewi Anna Sari Harahap; Imsar Imsar (Universitas Muhammadiyah Metro, 2023)
The purpose of this study was to identify and analyze the management and accountability of election funds in Deli Serdang Province. The analytical method used is data collection method, qualitative descriptive with interviews or documentation. Based on the results of the Deli Serdang Regency Election Grant Survey 2019, the Deli Serdang Regency Election Grant Accountability System was carried out according to established procedures. The mechanism for obtaining a grant from the Derisul Regency Government begins with Baisul sending an application to the Regency Government. The requirements include records of payment of funds (NPHD), receipts, facts of completeness, bank accounts in the names of additional grant recipients, payment processing, use, and accountability, namely PPK and bookkeeping of expenses. PNS status by the Regional Government of Deli Serdang Regency.